Exploring and expanding learning processes in sustainable agriculture workplace contexts - Mukute, Mutizwa (Rhodes University, Faculty of Education, Department of Education, 2010)
The focus of this study is to explore and expand farmer learning processes in sustainable agriculture workplace contexts. It examines change oriented learning processes in the context of three sustainable agriculture practices. The study begins by discussing the history and emergence of environmental discourses and approaches; sustainable agriculture; and the histories of three kinds of sustainable agriculture practices: Permaculture, Organic Farming and Machobane Farming System. It also traces the evolution of agricultural extension approaches within the wider context of education for sustainable development. The main focus of the study is an exploration of how farmer learning can be mediated through an expansive learning process. The study methodology surfaces some of the contradictions in sustainable agriculture and learning activity systems that farmers encounter in learning and practising sustainable agriculture. It uses these contradictions as sources of expansive learning in and between the respective activity systems of farmers, sustainable agriculture facilitators, agricultural extension workers (conventional) and organic entrepreneurs. As shown in the study, the expansive learning processes result in the modelling, implementation and reviewing of solutions to contradictions being faced in the learning and practice of sustainable agriculture. The study also proposes a number of tools that can be adapted and used by development farmers and agricultural trainers to examine and expand learning as well as build farmer agency. The study was conducted in three case study sites in Lesotho, South Africa and Zimbabwe. In Zimbabwe the study is located in Hwedza district in the St Margaret Primary School and community that learn, practise and facilitate the learning of Permaculture within the Schools and Colleges Permaculture Programme (SCOPE). The second study site is in South Africa: Durban urban and peri-urban areas where a community of organic farmers, facilitators and entrepreneurs coordinate the marketing of their produce through Isidore Farm and Earth Mother Organic and support each other to learn and practise organic farming. The third study site is based in the Mafeteng and Mohale"Ÿs Hoek districts of Lesotho where the focus was on farmers who learn and practise the Machobane Farming System (MFS) and are supported in this by the Rural Self Development Association (RSDA) and the Machobane Agricultural Development Foundation (MADF). Drawing on three sensitising concepts of dialectics, reflexivity and agency, the study worked with Cultural Historical Activity Theory (CHAT) underpinned by critical realism to reveal how farmer learning is mediated and expanded. The theory of practice/habitus also provided a useful theoretical lens with which to examine data generated. Using a two-phased, multiple embedded case study approach, the study worked within the broad framework of social learning. It used semi-structured individual and group interviews, observations and document analysis to explore learning processes and generate mirror"Ÿ data. This data was then used in Change Laboratory Workshops, within the Developmental Work Research methodology, where double stimulation and focus group discussions contributed to expanding learning processes. Drawing on critical realism the study used inductive, abductive and retroductive modes of inference to analyse data in each case study as well as across case studies. The findings of the study reveal that farmer learning is influenced by both intrinsic motives, such as identity, and extrinsic motives which are primarily associated with economic, ecological and health benefits. Farmers learn through scaffolding and mediating tools that link everyday and scientific knowledge. They also learn from fellow farmers through observation, practising and experimentation. Some of the issues that were raised in connection with farmer learning processes are: language; time to learn, practice and appropriate concepts; time to improve the natural resource base while at the same time improving income generation; and responses to climate change. The study also found that farmer learning and practice of sustainable agriculture in the case studies investigated, is influenced by past and current agricultural and educational policies; societal values and attitudes; social and cultural backgrounds; work affordances and gender relations; quality of training offered; poverty; and, HIV and AIDS. In the second phase of the study, which built on the problematic situations being encountered by research participants (sustainable agriculture farmers, sustainable agriculture facilitators, extension workers, and organic marketers) to surface contradictions, the main finding was that the expansive learning process has potential to enhance farmer learning and practice of sustainable agriculture. It does this by mobilising distributed cognition among participants as well as their preparedness to act. Through the expansive learning processes in each case study, research participants were able to question their practices, surface contradictions, model solutions and implement them, and thus build individual, collective and relational agency reflexively. Observation of this required micro-analysis of agentive talk and reflective talk. The study contributes in-depth insight into participatory research and learning processes, especially within the context of people-centred learning and innovation in the agricultural development arena. It provides empirical and explanatory insight into how change oriented social learning can emerge and be expanded in Education for Sustainable Development, explaining learning and change relationships in three sustainable agricultural practices. It also provides learning and extension tools to work with contradictions that arise from intentionality, experience, context and history in farming and training activity systems. Its key contribution lies in providing in-depth insight into mobilisation of human agency and reflexivity in change oriented sustainable agriculture learning and development, processes that are critical for responding to contemporary socio-ecological issues and risks.
Keywords: Sustainable agriculture -- Africa, Southern; Sustainable development -- Study and teaching -- Africa, Southern; Permaculture -- Zimbabwe; Organic farming -- South Africa; Farmers -- Social conditions -- Africa, Southern; Farmers -- Economic conditions -- Africa, Southern; Farmers -- Training of -- Africa, Southern